Does ankle plantar and dorsiflexion affect fifty-meter swimming time in swimmers? - İsmet Alagöz; Sema Can; Erkan Demirkan; Tuğrul Özkadı (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to determine the relationships between ankle plantar and dorsiflexion and the four swimming styles in girl and boy swimmers. The study consisted of 20 girls (Mage= 16.50 ± 0.51 years) and 20 boys (Mage= 16.50±0.51 years), for a total of 40 swimmers volunteer individuals. Anthropometric and body composition measures were obtained including body height, body mass, fat %, fat free mass (FFM). Besides, ankle flexibility was assessed by measuring ankle plantar flexion and ankle dorsiflexion and four style swimming performance was obtained in official competition. All values are presented as mean ±SD and median (min – max). Student t-test was performed on each independent variable to compare differences between the genders for the parametric test, for the nonparametric tests, it was used Mann Whitney U test. For the correlation analysis between two variables, Pearson correlation coefficients were used to describe correlations for the parametric variables, spearman’s correlation coefficients were used for the non-parametric variables. Significant high and moderate level of correlations was found between ankle plantar flexion, dorsiflexion (right and left), and average flexion and four style swim time in girl swimmers (p lt;0.001). In boy swimmers, there was found a moderate level of correlation between left, and average ankle dorsiflexion except right ankle dorsiflexion and swimming time for all styles (p lt;0.05). In conclusion, the study findings especially point towards the potential importance of ankle plantar and dorsiflexion in 50 m swimming time for all styles in girl swimmers.